A theoretical model of dentinogenesis: dentin and dentinal tubule formation (2013)
Dentinogenesis, odontoblast dentin formation, includes dentinal growth, mineralization and dentinal tubule formation. Odontoblasts synthesize collagen resulting in collagen apposition contributing to dentinogenesis. Furthermore, within the tubule, they express non-collagenous proteins, such as dentin phosphoprotein (DPP), associated with hydroxyapatite crystal formation and growth. The aim of this work was to determine patterns of growth and dentin formation and quantification of its mineralization. Findings from our work are relevant to endodontics for future regenerative treatment. We formulated a 3D domain mathematical model, which recreates the events that lead to dentinal tubule mineralization. As reference we used collagen apposition and DPP activity. We obtained a model depicting predentin's mineralization distribution during dentin development. Furthermore, we verified different DPP diffusion coefficients to test the model's sensitivity. We present a model to shed light on the process of dentin and dentinal tubule formation, and its relation to diffusion and mineralization processes.